THE IMPORTANCE OF USING TPR METHOD AND PROPER MATERIALS IN TEACHING YOUNG LEARNERS (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
This paper explores the application of Total Physical Response (TPR) in English language instruction, focusing on its effectiveness with young learners. TPR's integration of physical activity and verbal commands is examined as a means of enhancing comprehension, vocabulary acquisition, and overall student engagement. The study analyzes the versatility of TPR, demonstrating its adaptability to various learning contexts and its ability to cater to different learning styles. Furthermore, the paper investigates the positive impact of TPR on reducing learner stress and fostering a motivating learning environment. The findings support the conclusion that TPR constitutes a valuable pedagogical approach, particularly for young learners, contributing significantly to both language acquisition and overall learner development.